O poder do fã de nomear: um olhar para a etiquetagem social em plataformas de fanfics - Ferreira, Bruna Letícia (Universidade Federal de São Carlos, 2023)
Collaborative digital environments are growing and increasingly an option for browsing and daily consumption of content on the Web. Because they are meeting and interaction environments for people and groups with common interests, they are part of people's daily lives. In the context of fanfics, collaborative environments dedicated to the insertion of works, exchange of information between community members, dissemination and access to materials of the genre have gained evidence in recent years, which makes us question whether the fanfiction platforms used by Brazilian fans have guidelines intended for social tagging? In this sense, the objective is to investigate the process of social labeling on fanfict platforms that are most prominent on the national scene. This is an exploratory and descriptive research, with a qualitative approach and an applied nature. As for the procedures, a bibliographical research is carried out to discuss, from the Library and Information Science literature, the social labeling and the phenomenon of fanfiction as a fictional narrative written and disseminated by fans. Subsequently, the process of social tagging on Nyah! Fanfictions, Wattpad and Spirit Fanfiction, noting that fanfic platforms have basic guidelines on the insertion of fanfics in the environment, but there are no more specific mentions about the choice and attribution of tags for the representation of the contents of the works. The analysis made it possible to propose suggestions for improving the tagging process on fanfic platforms. Therefore, these platforms monitor how users are using categories and tags to describe their fanfics; revise the most popular tags and add new ones, which can also occur through user feedback and not just by platform moderators. Moreover, adoption of the hybrid model for the social tagging process is also an interesting action, as it combines exhaustiveness (which will occur through the tags assigned by ficwriters) and specificity (expansion of categories and genres in current taxonomies). It is concluded that the improvement of the social tagging process on fanfic platforms can be favored with the adoption of actions aimed at tagging by ficwriters (choice and attribution of tags), which requires a more strategic look on the part of moderators on content representation and its correlation with information retrieval.
The power of the fan to name: a look at social tagging on fan fiction platforms
Keywords: Representação da informação; Etiquetagem social; Plataformas de fanfiction; Information representation; Social tagging; Fanfics; Fanfiction platforms; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA